Penerapan Metode SQ3R Berbasis Audio Visual Untuk Menguatkan Keterampilan Membaca Siswa Kelas IV di Sekolah Dasar - Sandika Wena; Latif Latif (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Reading skills are a fundamental ability essential to the learning process in elementary school, yet many students still struggle to understand reading passages due to low interest and concentration. This study aims to analyze the planning, implementation, and improvement of fourth-grade students’ reading skills through the application of the audio-visual–based SQ3R method at SDN 003 Padang Sawah Kampar. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of the planning, action, observation, and reflection stages. The subjects of the study were 28 fourth-grade students and their teacher, using instruments such as teacher observation sheets, student observation sheets, and reading skill tests. The results showed a significant improvement in students’ reading skills from cycle I to cycle II, in which teacher activity increased from the “adequate” category to “very good,” student activity increased from “moderately active” to “highly active,” and classical mastery reached 82.14%. Based on these findings, it can be concluded that the implementation of the audio-visual based SQ3R method is effective in improving elementary school students’ reading skills.